Vitamin D metabolism-related single nucleotide polymorphisms in Chronic Obstructive Pulmonary Disease risk - Rojo-Tolosa, Susana; Pineda-Lancheros, Laura Elena; Fernández-Alonso, Andrea; Márquez-Pete, Noelia; Cura, Yasmin; Membrive-Jiménez, Cristina; Iglecias-Marangoni, Luciana Maria; Ramírez-Tortosa, MCarmen; Gálvez-Navas, José María; Pérez-Ramírez, Cristina; Morales-García, Concepción; Jiménez-Morales, Alberto (Frontiers in Endocrinology, 2024)
Introduction: Chronic obstructive pulmonary disease (COPD) is one of the world's major public health problems. It is characterized by a major inflammatory response, where vitamin D, due to its role in regulating the immune system, and genetic variants involved in its metabolism may play an essential role. The aim of this study is to evaluate the association between 13 polymorphisms related to vitamin D metabolism and the COPD risk. Material and methods: A retrospective longitudinal study was designed in which 152 cases of COPD diagnosed at the University Hospital Virgen de las Nieves and 456 controls without the pathology, matched by age and sex, were included. The determination of the 13 polymorphisms was carried out using TaqMan™ probes. Results: Statistical analysis showed that the AA genotype and the A allele of the CYP27B1 rs4646536 polymorphism may be associated with an increased risk of developing COPD according to genotypic models (OR =